Outcomes of pregnancy complicated with hyperthyroidism: A cohort study - Suchaya Luewan (2018)
Objective: To determine maternal and fetal outcomes of women complicated with hyperthyroidism compared with those in normal pregnant women. Materials and methods: This cohort study was conducted on singleton pregnant women complicated by hyperthyroidism without other medical complications between January 1994 and December 2008, at tertiary center. The normal controls were identified to match the cases with the ratio of 2:1. The baseline characteristics as well as maternal and fetal outcomes were analyzed and compared for pregnancy outcomes. Results: Of the 203 pregnant women diagnosed for hyperthyroidism, 180 cases met the inclusion criteria, and 360 controls were matched. The activity of the disease was controlled to be euthyroid state in most cases. Maternal complications were comparable between both groups except that the study group had potentially higher incidence of pregnancy-induced hypertension. The mean gestational age (±SD), and mean birth weight were significantly lower in the study group. The incidence of fetal growth restriction, fetus with low birth weight and preterm births were significantly higher in the study group with a relative risk of 1.3, 1.4, and 1.3, respectively. Conclusion: Pregnant women with hyperthyroidism were significantly associated with an increased risk of fetal growth restriction, preterm birth and low birth weight and had a tendency to have a higher rate of pregnancy-induced hypertension. © 2010 Springer-Verlag.